Pengaruh Profit Sharing Terhadap Produktivitas Usaha Mikro dan Kecil di Indonesia - Dhonna Widya Poernamasari (Airlangga Journal of Innovation Management, 2023)
Research on the effect of profit-sharing on large-scale enterprise productivity has been done in many countries. But previous study found an inconsistent results, that is profit sharing is not significantly influence productivity of MSMEs. This research aims to deepen more about the reason is  this profit-sharing in its application have or don't have a significant impact in increasing productivity of Micro and Small Enterprises in Indonesia. The qualitative research method used in this research is through in-depth interview techniques to seven respondents who are MSME entrepreneurs in the manufacturing sector with product types that vary between respondents. The purpose of this interview is to gather information about the system of wages and distribution of bonuses in MSMEs, which have different characteristics from large industries in general. The interview results show that there is profit sharing in Indonesia MSMEs, but it is not considered as financial compensation or work bonus that leads to the next performance target. However, most of them interpreted as "kindness" from MSME owners in form of financial or non-financial benefits. This research brings research implication that profit sharing on MSMEs are unique and can be applied in many forms. Even though in previous quantitative study, profit sharing is stated as not significantly influence the MSMEs productivity and performance, In some cases, profit sharing is proven to increase the motivation and loyalty of employees.